Analysis of Ornamental Fish (Pomacanthus navarchus) for the Sustainability of Small and Medium Enterprises (UKM) in South Sulawesi, Indonesia - Ilham, Ilham; Natsir, Andi Baso Adil (International Journal of Education, Vocational and Social Science, 2023)
Pomacanthidae is a marine ornamental fish species that has become a favourite for both domestic and global markets. Ornamental fish enthusiasts have now spread across all walks of life. Although the purchasing power of people varies (depending on the class), this is enough to prove that all circles of society are fond of ornamental fish as a business field. The purpose of this study is to analyse the various factors affecting the export of angel pyama angel fish in South Sulawesi and to analyse the various factors affecting the supply of angel pyama fish. The types and sources of data needed in this study consist of Primary Data and Secondary Data. Local price and cost of production of angel pyama and batman fish have a significant positive effect on the amount of production/supply of angel pyama fish and the local price of angel batman fish has a significant negative effect on the amount of angel pyama fish production. The export price of angel pyama fish has a significant negative effect on the amount of export demand for angel pyama fish while the export price of angel batman fish has a significant positive effect on the amount of export demand for angel pyama fish. The exchange rate of the rupiah against the US dollar has no significant effect on the amount of export demand for angel pyama fish while the export price of angel pyama fish and the exchange rate of the rupiah against the US dollar has a significant effect on the amount of export demand for angel pyama fish.